Application of Micro-alga Tetradesmus nygaardi for Wastewater Quality Improvement - Qader, Muzhda; Shekha, Yahya (Al-Nahrain Journal of Science, 2024)
Microalgae have been increasingly used for wastewater treatment due to their capacity to assimilate nutrients. Samples of wastewater were taken from the Erbil wastewater channel near Dhahibha village. To investigate the role of algae in wastewater treatment algal samples were collected and used to isolate the most dominant and pollution tolerant algae such as Tetradesmus nygaardi cultures in BG11 broth and used for the treatment. Three doses (2, 1, and 0.2 g. l-1) of micro-algae Tetradesmus nygaardi were applied for this experiment for 21 days, and samples were periodically (every 3 days) analyzed for physicochemical parameters such as pH, EC, phosphate, nitrate, and BOD5 using standard methods, in addition to, chlorophyll a determination. Results showed that the highest dose (2g.l-1) was the most effective for removing the highest rate of nutrients, which was confirmed statistically with significant differences (p≤0.05) between all doses. Ammonium had the highest removal rate of 96 %, followed by NO3 at 95%, while BOD5 had a range of 82 to 89.5%. Results showed that the highest dose 2g.l-1 was the most effective dose for removing nutrients, confirmed by significant differences (p≤0.05) between all doses. Reduced nutrient levels were accompanied by an increase in chlorophyll content, with the greatest biomass production of 1.03 mg. l-1 on the 17th day of the experiment.